Pengaruh Penerapan E-Filling Perpajakan, Kualitas Pelayanan, Kesadaran Wajib Pajak, dan Sanksi Perpajakan pada Kepatuhan WPOP - Mahendra, I Putu Ardhian Janu; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p09, 2020)
This study aims to determine the effect of e-filling forwarding, quality, taxpayer awareness, and tax sanctions on individual taxpayer compliance at East Denpasar KPP. The data analysis method used is multiple linear regression. The results of this study indicate that the good application of e-filling, quality of service, awareness of taxpayers, and tax penalties have a significant effect on the compliance of individual taxpayers who are registered at the East Denpasar KPP. This research can be used as a motivation for KPT Prtama East Denpasar to be able to maintain good service quality for the satisfaction and comfort of taxpayers to carry out their tax obligations. Keywords: Application of E-Filing; Service Quality; Taxpayer Awareness; Tax Sanctions; Obedience.